Atopic dermatitis or Hyper IgE syndrome? - Filotico, R.; Martire, B.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2015)
The dermatitis of Hyper IgE syndrome is characterized by involvement of the axillary and inguinal folds and follicular rash. In addition to the high IgE levels (> 2,000 IU/ml), important for the diagnosis are severe and recurrent skin and lung infections. However, less severe cases without lung involvement have been reported (3). Also important are brittle bones, dental abnormalities and coarse facies. The differential diagnosis beween atopic dermatitis and Hyper IgE syndrome is easy in familial cases, difficult in sporadic cases. The “scoring” system of Grimbacher et Al. (2) fixed conventionally a high limit, above which the diagnosis of Hyper IgE syndrome is likely, and a low limit, below which the diagnosis is unlikely. In between is a wide indeterminate area, in the context of which it is impossible to be sure of the diagnosis. Diriment is the demonstration of a STAT3 or DOCK8 deficiency.